Impact of the implementation of classroom workshop creative methodology in promoting of creative capacity in pre-school education - Klimenko, Olena (Pensando Psicología, 2010)
The article presents results of research whose purpose was aimed at the creative capacity of the preschool students. The objective of the study was to analyze the impact of implementation of methodology classroom workshop creative scores test crea by children aged between 6 and 7 years. According to the methodology is a preexperimental design, where working with groups untouched, natural study, according to his purpose this research is classifi ed as a pedagogical research because it went to look for the formative, act through design and implementation of methodological proposals and their relation to the development of the creative ability in preschool students. Study developed a methodological proposal for classroom.Workshop creative, based on the historical-cultural approach oriented to encourage creativity in childrenof preschool. This proposal was transmitted to teachers through a programme of training consisting of threemodules: theoretical, methodological and attitude. Results obtained made it possible to demonstratethat the methodological proposal for classroom implementation creative workshop focused signifi cantlyin the scores for the crea test by children from 6 to 7 years; at the same time that impact did not providea meaningful relationship with variable gender, age and socioeconomic status of students. According tothese results concluded that it is possible to build some components of the creative capacity from pre-schoolthrough implementation of methodological proposals especially designed for this purpose and implementedteachers training.
Keywords: creative ability; teaching practice; didactic strategies of cognitive and emotional mediation